A study on ionospheric scintillation near the EIA crest in relation to equatorial electrodynamics. Issue 2 (12th February 2014) - Chatterjee, S.; Chakraborty, S. K.; Veenadhari, B.; Banola, S.
Abstract Equatorial electrojet (EEJ) data, which are considered as a proxy index of equatorial electric field, are analyzed in conjunction with equatorial ionosonde, total electron content (TEC) and scintillation data near the equatorial ionization anomaly (EIA) crest for the equinoctial months of high solar activity years (2011–2012) to identify any precursor index of postsunset evolution of equatorial electron density irregularities and subsequent occurrence of scintillation near the northern EIA crest. Only geomagnetically quiet and normal electrojet days are considered. The diurnal profiles of EEJ on the scintillation days exhibit a secondary enhancement in the afternoon to presunset hours following diurnal peaks. A series of electrodynamical processes conducive for generation of irregularities emerge following secondary enhancement of EEJ. Latitudinal profile of TEC exhibits resurgence in EIA structure around the postsunset period. Diurnal TEC profile near the EIA crest resembles postsunset secondary enhancement on the days with afternoon enhancement in EEJ. Occurrence of equatorial spread F and postsunset scintillation near the EIA crest seems to follow the secondary enhancement events in EEJ. Both the magnitude and duration of enhanced EEJ are found to be important for postsunset intensification of EIA structure and subsequent occurrence of equatorial irregularities. A critical value combining the two may be considered an important precursor for postsunset occurrence of scintillation near the EIA crest. The results are validated using archived data for the years 1989–1990 and explained in terms of modulation effects of enhanced equatorial fountain.